LATIHAN LARI ANGKAT PAHA, LOMPAT TEPUK, PUSH-UP DENGAN POLA CIRCUIT TRAINNING TERHADAP PENINGKATAN KESEGARAN JASMANI - SUPRIYANTO, (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Basketball extracurricular activities in junior high schools 2 Ketapang district Sampang, students seem less eager to follow the material in any given workout. This is because the condition of the students' level of physical fitness is not good, and is unable to perform activities of basketball practice until the end. For that is expected for extracurricular basketball teachers and trainers should be able to provide many alternative forms of training models that are improved physical fitness. With a running exercise thigh lift, skip pat, push-ups are packed with circuit design trainning then a student can develop strength, endurance, and overall physical fitness. The purpose of this study was to determine the effect of exercise running up the thighs, pat down, push-ups with a circuit design training to increase students' physical fitness, extracurricular basketball participants. Objectives of this study were students of junior high schools 2 Ketapang extracurricular basketball Sampang Ketapang district and the number of study subjects included a total of 27 students: 15 boys and 12 students daughters. The method in this analysis using statistical methods and quantitative comparative desikriptif. Conclusion The results of the study are: Exercise Running thigh lift, jump pat, push-ups with circuit training design significantly influence students' physical fitness improvement, the results of the t test showed tcount 6.871 > 2.056 ttable value. Providing training run thigh lift, jump pat, push-ups with circuit training patterns can improve physical fitness of students in extracurricular basketball junior high schools 2 Ketapang District Sampang 10.0%. Keywords: Exercise Circuit Training, Physical Fitness.